Getting Out of School and into the Workplace : Strengthening Work-Based Learning in Upper Secondary Technical Education in Poland's Swietokrzyskie Region - Hoftijzer, Margo; Stronkowski, Piotr; Rozenbaum, Jakub (Washington, DC: World Bank, 2018)
The potential for work-based learning to improve the quality and relevance of vocational education and training is widely recognized. Work-based learning allows students to develop skills and gain experience through practical, real-life experiences in the workplace, complementing what is being learned in the classroom. However, many vocational education and training systems worldwide are still largely school-based and do not incorporate much work-based learning. There are many studies of mature training systems that are already largely employer-driven and firm-based, but less is known about how school-based vocational education and training systems can best transition to including stronger elements of work-based learning.